Iron mineralization and core dissociation in mammalian homopolymeric H-ferritin: Current understanding and future perspectives - Melman, Artem; Bou-Abdallah, Fadi (Biochimica et biophysica acta. General subjects, 2020)
The mechanism of iron oxidation and core formation in homopolymeric H-type ferritins has been extensively studied in-vitro, so has the reductive mobilization of iron from the inorganic iron(III) core. However, neither process is well-understood in-vivo despite recent scientific advances. Here, we provide a summary of our current understanding of iron mineralization and iron core dissolution in homopolymeric H-type ferritins and highlight areas of interest and further studies that could answer some of the outstanding questions of iron metabolism. The overall iron oxidation mechanism in homopolymeric H-type ferritins from vertebrates (i.e. human H and frog M ferritins) is similar, despite nuances in the individual oxidation steps due to differences in the iron ligand environments inside the three fold channels, and at the dinuclear ferroxidase centers. Ferrous cations enter the protein shell through hydrophilic channels, followed by their rapid oxidization at di‑iron centers. Hydrogen peroxide produced during iron oxidation can react with additional iron(II) at ferroxidase centers, or at separate sites, or possibly on the surface of the mineral core. In-vitro ferritin iron mobilization can be achieved using a variety of reducing agents, but in-vivo iron retrieval may occur through a variety of processes, including proteolytic degradation, auxiliary iron mobilization mechanisms involving physiological reducing agents, and/or oxidoreductases. This review provides important insights into the mechanisms of iron oxidation and mobilization in homopolymeric H-type ferritins, and different strategies in maintaining iron homeostasis. Iron Oxidation Mechanism in Human H Ferritin. From top left and counterclockwise, (1,2) diferrous and oxygen-bound diferrous-protein complex, (3, 4) deprotonated and protonated peroxo diFe(III)-protein complexes, (5) μ-oxo-diFe(III) protein complex. [Display omitted] •Ferrous cations enter the ferritin shell through hydrophilic channels.•Rapid Fe(II) oxidization occurs at the di‑iron ferroxidase centers.•H2O2 can react with Fe(II) at ferroxidase centers, at separate sites, or on surface of the iron core.•In-vitro ferritin iron mobilization can be achieved using a variety of reducing agents.•In-vivo iron retrieval includes proteolytic degradation and possible iron reductive mechanisms.